2012
DOI: 10.1242/dev.065581
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 and Mitf cross-regulatory interactions consolidate progenitor and melanocyte lineages in the cranial neural crest

Abstract: SUMMARYThe cellular origin and molecular mechanisms regulating pigmentation of head and neck are largely unknown. Melanocyte specification is controlled by the transcriptional activity of Mitf, but no general logic has emerged to explain how Mitf and progenitor transcriptional activities consolidate melanocyte and progenitor cell fates. We show that cranial melanocytes arise from at least two different cellular sources: initially from nerve-associated Schwann cell precursors (SCPs) and later from a cellular so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
153
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(179 citation statements)
references
References 58 publications
22
153
0
1
Order By: Relevance
“…However, our data on melanocyte migration toward their target location in the cochlea, which to our knowledge has not been shown before in such clarity, suggests that cochlear melanocytes in humans migrate through the periotic mesenchyme from the opposite side. In agreement, several studies in mice embryos show the presence of neural crest derivatives or melanocytes near this part of the otic vesicle around embryonic day 10.5 (Steel et al, 1992; Freyer et al, 2011; Adameyko et al, 2012; Wakaoka et al, 2013; Sandell et al, 2014). Therefore, although the peripheral glial cells in the cochlea originate from the migratory wave of neural crest cells from rhombomere 4, we now hypothesize that cochlear melanocytes originate from a different wave of neural crest cells, namely those delaminating from the region at rhombomere 6, at the location of the developing glossopharyngeal nerve (cranial nerve IX) and the third pharyngeal arch.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, our data on melanocyte migration toward their target location in the cochlea, which to our knowledge has not been shown before in such clarity, suggests that cochlear melanocytes in humans migrate through the periotic mesenchyme from the opposite side. In agreement, several studies in mice embryos show the presence of neural crest derivatives or melanocytes near this part of the otic vesicle around embryonic day 10.5 (Steel et al, 1992; Freyer et al, 2011; Adameyko et al, 2012; Wakaoka et al, 2013; Sandell et al, 2014). Therefore, although the peripheral glial cells in the cochlea originate from the migratory wave of neural crest cells from rhombomere 4, we now hypothesize that cochlear melanocytes originate from a different wave of neural crest cells, namely those delaminating from the region at rhombomere 6, at the location of the developing glossopharyngeal nerve (cranial nerve IX) and the third pharyngeal arch.…”
Section: Discussionsupporting
confidence: 69%
“…As cochlear development in humans progresses slower than in mice (as a rule of thumb, one day of rodent cochlear development corresponds to one week in humans), this permits a more explicit visualization of developmental events. Recently, it has been reported that cranial melanocytes can arise from Schwann cell precursors migrating together with outgrowing nerves (Adameyko et al, 2009; Adameyko et al, 2012). As Schwann cell precursors arrive in the cochlea via the cochlear nerve (Sandell et al, 2014), it is tempting to propose that melanocytes (precursors) may travel along the same path.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies, miR-638 was found to protect melanoma cells from apoptosis and autophagy [25], and promote starvation-or rapamycin-induced autophagy in ESCC and breast cells (KYSE450 and MCF-7) [26]. SOX2, a member of SRY-related HMG-box transcription factors families, is a well-established regulator of cell differentiation and development [27,28]. More than that, accumulating studies suggest that SOX2 acts as an oncogene in some cancers, such as skin squamous-cell carcinoma [29,30], lung squamouscell carcinoma [31,32], ovarian carcinoma [33], osteosarcomas [34] and glioblastoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…These melanocytes differentiate at late stages relative to pigment cells directly generated from the NC. Thus, in addition to late emigrating/early differentiating NC-derived melanocytes, a subset of early delaminating NC cells that migrate dorsoventrally and later become SCPs in association with the growing nerves can develop either into mature SCs if they remain in contact with nerve fibers or generate melanocytes if they detach from the nerve environment (3,9,10). Except for their common origin from the NC, the relationship between these two melanocyte subsets, at both cellular and molecular levels, remains to be elucidated.…”
mentioning
confidence: 99%